2015
DOI: 10.1159/000440764
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Renal Pelvis as a Result of Long-Standing Staghorn Calculi

Abstract: We report on a 79-year-old woman with staghorn calculi who presented with severe hypercalcemia. She was later found to have humoral hypercalcemia of malignancy caused by a rare tumor, squamous cell carcinoma of the renal pelvis. Chronic irritation, infection and inflammation from staghorn stones cause squamous metaplasia, leading to squamous cell carcinoma of the renal collecting system. The prognosis is very poor, with a 5-year survival rate of <10%. This case highlights the importance of awareness of a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The most common subtypes of renal cancer are clear cell carcinoma and chromophobe, respectively, and SCC is the rarest subtype. Urothelial SCC is more common in cases aged 50 -70 years and in women (1) demonstrations and signs are nonspecific and include fever, weight loss, pain in the flank area, obstructive uropathy, hematuria, and paraneoplastic syndromes (4,5). According to the non-specificity of Xantogranolomatous pyelonephritis (XGP), symptoms, pyonephrosis, and chronic pyelonephritis are in the differential diagnosis list of this disease (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common subtypes of renal cancer are clear cell carcinoma and chromophobe, respectively, and SCC is the rarest subtype. Urothelial SCC is more common in cases aged 50 -70 years and in women (1) demonstrations and signs are nonspecific and include fever, weight loss, pain in the flank area, obstructive uropathy, hematuria, and paraneoplastic syndromes (4,5). According to the non-specificity of Xantogranolomatous pyelonephritis (XGP), symptoms, pyonephrosis, and chronic pyelonephritis are in the differential diagnosis list of this disease (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound diagnosis of the disease is difficult due to non-specific findings, such as hydronephrosis and calcification. For this reason, it is helpful to use CT scans in suspected cases (5,9). Renal SCC is usually seen as a large, necrotic, and ulcerative mass with a clear invasion to surrounding tissues on gross specimens (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Renal SCC is also difficult to be diagnosed in the early stages due to its non-specific symptoms, radiological examination findings, and the absence of tumor markers. [3][4][5][6] Chronic kidney disease and kidney cancer are considered to be renal disorders associated with nephrolithiasis. A study conducted by Keddis and Rule showed that individuals with a history of nephrolithiasis may have 2-3 times the potential to suffer from chronic kidney disease in the future.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Other studies also mention that chronic irritation, inflammation, and infection caused by staghorn stones are believed to induce reactive changes in urothelial or renal pelvic epithelial cells that lead to the development of neoplasia through the process of metaplasia and leukoplakia and may eventually develop into SCC. 3,4,10,12,13 The incidence of SCC accompanied by the presence of urinary tract stones varies greatly, starting from 18% in the USA to 100% in Hong Kong. 4,14 The initial diagnosis of SCC is sometimes difficult, especially when kidney stones present, since both the symptoms and radiological features will be obscured by those of the kidney stones, and the imaging studies will only reveal the finding of the stones or hydronephrosis due to obstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation